Effects of hot-fat trimming on retail display color of three beef muscles - S.R. Stuewe; Donald H. Kropf; Melvin C. Hunt; R.E. Campbell; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1995)
Steaks from subprimal cuts from carcass sides that were either hot-fat-trimmed to .25 inch or not hot-f at-trimmed (control) were used to determine trimming effects on retail display color. After 14 days storage in vacuum bags at 30EF, subprimals were cut into 1-inch-thick steaks for evaluation. Specific muscles that were evaluated were the loin strip (longissimus lumborum) , inside round (semimembranosus only), an d the chuck clod (triceps brachii only). The steaks were packaged in polyvinylchloride (PVC) film and displayed. The loin strip steaks from hot-fat-trimmed sides were more discolored (P<.05) than from nontrimmed controls at 0, 3, and 4 days display, but both had acceptable color through 4 days of display. Treatments were not different for inside round steaks (P>.05) ; the deep location was less red (P<.05) than the location closer to the muscle surface. Chuck clod steaks were not affected by trimming (P>.05). The location closest to the muscle surface was brightest red, and the deep location was darkest (P<.05). All inside round and chuck clod steaks were unacceptable in appearance by day 3 of display. Hot-fat trimming did not degrade the display color of these two muscles and overall effect of hot-fat trimming on beef steak display life was minimal.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Color; Hot fat trim